A Systematic Review of Electrophysiological Findings in Binge-Purge Eating Disorders: A Window Into Brain Dynamics - Hiluy, Joao C.; David, Isabel A.; Daquer, Adriana F. C.; Duchesne, Monica; Volchan, Eliane; Appolinario, Jose C. (Frontiers in Psychology, 2021)
Binge-purge eating disorders (BP-ED), such as bulimia nervosa and binge eating disorder, may share some neurobiological features. Electroencephalography (EEG) is a noninvasive measurement modality that may aid in research and diagnosis of BP-ED. We conducted a systematic review of the literature on EEG findings in BP-ED, seeking to summarize and analyze the current evidence, as well as identify shortcomings and gaps to inform new perspectives for future studies. Following PRISMA Statement recommendations, the PubMed, Embase, and Web of Science databases were searched using terms related to “electroencephalography” and “binge-purge” eating disorders. Of 555 articles retrieved, 15 met predefined inclusion criteria and were included for full-text analysis. Eleven studies investigated EEG by means of event-related potentials (ERP) in BP-ED individuals: 7 using eating disorder-related stimuli (i.e., food, body image) and 4 using non-eating disorder-related stimuli (i.e., facial expressions or auditory clicks). These studies found significant differences in the N200, P200, P300, and LPP components in BP-ED participants compared to controls, indicating that this population exhibits impairments in selective attention, attentional allocation/processing, and allocation of motivational or emotion-based attention. Five studies investigated EEG using frequency analysis; reporting significant differences in beta activity in fronto-temporal and occipito-temporo-parietal areas in BP-ED individuals compared to controls, revealing a dysfunctional brain network. However, the small number of studies, the heterogeneity of samples, study paradigms, stimulus types, and the lack of an adequate assessment of neuropsychological parameters are some limitations of the current literature. Although some EEG data are promising and consistent with neuroimaging and neuropsychological findings in individuals with BP-ED, future studies need to overcome current methodological shortcomings.